SISTEM PENUNJANG KEPUTUSAN MULTI KRITERIA UNTUK PENGEMBANGAN AGROINDUSTRI KOPI GAYO MENGGUNAKAN PENDEKATAN FUZZY-ECKENRODE DAN FUZZY-TOPSIS - Rahmat Fadhil, M. Syamsul Maarif, Tajuddin Bantacut, Aji Hermawan (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
In multi-criteria decision making, accuracy in weighting for the determination of the various alternatives available criteria is always taken into account. The decision makers always face difficult choices in selecting options available. Hence, expert opinions are required as part of the decision making process. This study aimed to formulate a multi-criteria decision-making strategies and to propose priorities within Gayo coffee agroindustry development. A total of ten experts were involved to select various alternatives based on certain criteria that have been set. Weighting data analysis of the expert assessment conducted by Fuzzy-Eckenrode, whereas Fuzzy-Topsis method was used to determine alternative for Gayo coffee agroindustry development. This study found that Fuzzy-Eckenrode method was able to facilitate a good weighting result to determine a certain criterion in the consideration of Gayo coffee agroindustry development, and the application of the Fuzzy-Topsis approach provided a opportunity to find the main or the most ideal alternative of a Gayo coffee agroindustry development system. Based on the Fuzzy-Eckenrode approach, the highest weight founded was the assessment quality of various aspects that will be implemented. Meanwhile, form the Fuzzy-Topsis approach, it wasfound that institutional conduciveness as a priority in the Gayo coffee agroindustry development. Keywords: decision-making systems, fuzzy-eckenrode, fuzzy-topsis, gayo coffee, multi-criteria